Causes and Consequences of Child Marriage in Rural Bangladesh: A Qualitative Study on Meherpur District - Nishat Tasnim; Md. Sobur Hossain; Md. Zahidul Islam (Philippine Social Science Journal, 2024)
This study investigated the causes and consequences of child marriage in Meherpur District, Bangladesh. Researchers conducted in-depth interviews with 20 respondents to understand this complex issue. Poverty, lack of education, family instability, and societal pressure emerged as significant factors contributing to child marriage. The study also reveals how cultural factors, including superstitions, religious interpretations, and traditional practices, perpetuate this harmful practice. Findings indicate that child marriage negatively impacts girls' physical and mental health, often leading to health complications and psychological trauma. This research highlights the urgent need for interventions that empower girls, promote education, and address the root causes of child marriage in Meherpur District.